2022
DOI: 10.3389/fpubh.2022.1026393
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the use of mobile phones to access reproductive health care services in Tamale, Ghana

Abstract: IntroductionAfrica has one of the world's highest populations of young people. In addition, Africa has one of the highest proportions of young people facing the worst health challenges. Although previous scholars have reported that young people were using mobile phones to fill in the gaps in accessing reproductive health services, among other health services, there was little comprehensive research on the perception of young people in Tamale, Ghana, on the use of mobile phones to access reproductive health ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
3
0
1
Order By: Relevance
“…This positive effect implies that a 1% increase in farmers producing other crops than maize will result in a 42.76% increase in farmers' decisions to adopt CSA. These results are consistent with research by Agbenyo et al [60] that showed that crop diversification is a key factor in CSA strategies to support resilience towards climate change.…”
Section: Discussionsupporting
confidence: 93%
“…This positive effect implies that a 1% increase in farmers producing other crops than maize will result in a 42.76% increase in farmers' decisions to adopt CSA. These results are consistent with research by Agbenyo et al [60] that showed that crop diversification is a key factor in CSA strategies to support resilience towards climate change.…”
Section: Discussionsupporting
confidence: 93%
“…This postive effect implies that, 1% increase in farmers producing other crops than maize will results in a 42, 76% increase in farmers decision to adopt CSA. These results are consistent with research by Agbenyo et al [37] that showed that crop diversification is a key factor in CSA strategies to support resilience towards climate change.…”
Section: Discussionsupporting
confidence: 93%
“…In line with this explanation, a study in Ghana revealed that in urban areas, access to and use of mobile phones enabled young people to overcome cultural barriers to exercise their sexual rights. 55 Similar results were observed for rural areas where women who used the Internet and those exposed to family planning messages (via texts or social media) were more likely to be able to ask their male partners to use condoms. This further echoes the importance of Internet use as a gateway to a trove of sexual and reproductive health information (including information on women's reproductive empowerment) and digital family planning messages for women's sexual agency.…”
Section: Discussionsupporting
confidence: 64%